Nkx2.5 Functions as a Conditional Tumor Suppressor Gene in Colorectal Cancer Cells via Acting as a Transcriptional Coactivator in p53-Mediated p21 Expression - Li, Huili; Wang, Jiliang; Huang, Kun; Zhang, Tao; Gao, Lu; Yang, Sai; Yi, Wangyang; Niu, Yanfeng; Liu, Hongli; Wang, Zheng; Wang, Guobin; Tao, Kaixiong; et al. (Frontiers in Oncology, 2021)
NK2 homeobox 5 (Nkx2.5), a homeobox-containing transcription factor, is associated with a spectrum of congenital heart diseases. Recently, Nkx2.5 was also found to be differentially expressed in several kinds of tumors. In colorectal cancer (CRC) tissue and cells, hypermethylation of Nkx2.5 was observed. However, the roles of Nkx2.5 in CRC cells have not been fully elucidated. In the present study, we assessed the relationship between Nkx2.5 and CRC by analyzing the expression pattern of Nkx2.5 in CRC samples and the adjacent normal colonic mucosa (NCM) samples, as well as in CRC cell lines. We found higher expression of Nkx2.5 in CRC compared with NCM samples. CRC cell lines with poorer differentiation also had higher expression of Nkx2.5. Although this expression pattern makes Nkx2.5 seem like an oncogene, in vitro and in vivo tumor suppressive effects of Nkx2.5 were detected in HCT116 cells by establishing Nkx2.5-overexpressed CRC cells. However, Nkx2.5 overexpression was incapacitated in SW480 cells. To further assess the mechanism, different expression levels and mutational status of p53 were observed in HCT116 and SW480 cells. The expression of p21WAF1/CIP1, a downstream antitumor effector of p53, in CRC cells depends on both expression level and mutational status of p53. Overexpressed Nkx2.5 could elevate the expression of p21WAF1/CIP1 only in CRC cells with wild-type p53 (HCT116), rather than in CRC cells with mutated p53 (SW480). Mechanistically, Nkx2.5 could interact synergistically with p53 and increase the transcription of p21WAF1/CIP1 without affecting the expression of p53. In conclusion, our findings demonstrate that Nkx2.5 could act as a conditional tumor suppressor gene in CRC cells with respect to the mutational status of p53. The tumor suppressive effect of Nkx2.5 could be mediated by its role as a transcriptional coactivator in wild-type p53-mediated p21WAF1/CIP1 expression.